2022
DOI: 10.1038/s41598-022-05696-9
|View full text |Cite
|
Sign up to set email alerts
|

Classification of regular and chaotic motions in Hamiltonian systems with deep learning

Abstract: This paper demonstrates the capabilities of convolutional neural networks (CNNs) at classifying types of motion starting from time series, without any prior knowledge of the underlying dynamics. The paper applies different forms of deep learning to problems of increasing complexity with the goal of testing the ability of different deep learning architectures at predicting the character of the dynamics by simply observing a time-ordered set of data. We will demonstrate that a properly trained CNN can correctly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The method can estimate the largest Lyapunov exponent from noisy data, based on training deep learning models on synthetically generated trajectories 22 . The deep learning techniques were trained with different indexing methods based on chaos indicators, like Fast Lyapunov Indicators and the frequency map analysis 23 . The goal was to classify types of motion (series corresponds to a chaotic, librational, or rotational motion) by observing samples taken from time series coming from simple Hamiltonian systems.…”
Section: Background and Summarymentioning
confidence: 99%
“…The method can estimate the largest Lyapunov exponent from noisy data, based on training deep learning models on synthetically generated trajectories 22 . The deep learning techniques were trained with different indexing methods based on chaos indicators, like Fast Lyapunov Indicators and the frequency map analysis 23 . The goal was to classify types of motion (series corresponds to a chaotic, librational, or rotational motion) by observing samples taken from time series coming from simple Hamiltonian systems.…”
Section: Background and Summarymentioning
confidence: 99%
“…While many ML approaches exist, per the no free lunch theorem (NFL) Wolpert and Macready (1997), no single approach works best for all given problems Celletti et al (2020). Nevertheless, researchers strive to improve models and their methodologies to achieve the best possible general performance.…”
Section: Introductionmentioning
confidence: 99%
“…Tese types of perturbation systems have been the focus of interest by a number of authors and the references therein [1][2][3][4][5]. We mention in particular the works of Poincaré, regarding the three-body problem (these orbits were called "frst-view sort solutions") [6], and the studies by Ambrosetti et al [7] and Celletti et al [8] which showed the existence of a skew-T/2 periodic solution of the following problem:…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 1 (see [7,8,12]). Tere exists ε 0 > 0 such that ∀|ε| < ε 0 , the perturbed system (6), has at least one noncollision symmetric (skew-T/2 periodic) orbit near the circular orbit of (6).…”
Section: Introductionmentioning
confidence: 99%